DEVELOPMENT OF STUDENTS' CRITICAL THINKING ABILITY AND THE SPIRIT OF NATIONALISM THROUGH CITIZENCY EDUCATION - Fajar Arya; Muhammad Khoirur Rizqi (PRODI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN STKIP PGRI SUMENEP, 2024)
Citizenship education plays an important role in developing students' critical thinking skills and a spirit of nationalism. The aim of this research is to analyze more specifically citizenship education as an effort to improve students' critical thinking skills and the spirit of nationalism. This research uses a literature study method which is carried out by reviewing previous research through online journals. The results of this research are that citizenship education can improve students' critical thinking skills. Through forms of learning such as encouraging discussion and debate, teaching media literacy, focusing on investigation and problem solving, and emphasizing reflection and self-assessment, students can develop the skills of critical analysis, reasoning, information evaluation, and problem solving. Citizenship education in higher education plays a role in instilling nationalist values, strengthening shared identity, and building unity amidst diversity. Through this course, it is hoped that students can have a strong intellectual, religious, humanitarian and patriotism vision, and become an integral part in building a civilized society, nation and state.